RF and microwave microelectronics packaging II - Kuang, Ken; Sturdivant, Rick (Springer, 2017)
Reviews RF, microwave, and microelectronics assembly process, quality control, and failure analysis Bridges the gap between low cost commercial and hi-res RF/Microwave packaging technologies Engages in an in-depth discussion of challenges in packaging and assembly of advanced high-power amplifiers This book presents the latest developments in packaging for high-frequency electronics. It is a companion volume to "RF and Microwave Microelectronics Packaging" (2010) and covers the latest developments in thermal management, electrical/RF/thermal-mechanical designs and simulations, packaging and processing methods, and other RF and microwave packaging topics. Chapters provide detailed coverage of phased arrays, T/R modules, 3D transitions, high thermal conductivity materials, carbon nanotubes and graphene advanced materials, and chip size packaging for RF MEMS. It appeals to practicing engineers in the electronic packaging and high-frequency electronics domain, and to academic researchers interested in understanding the leading issues in the commercial sector. It is also a good reference and self-studying guide for students seeking future employment in consumer electronics.
Includes index.
Keywords: Microelectronic packaging.; elektronické knihy; electronic books